(untitled) - Hepworth, Dean H; Hepworth, Dean H (Belmont, CA, 2006)
Neal A. Newfield, Ph.D., LICSW (Giver) ; Rev. ed. of: Direct social work practice / Dean H. Hepworth, Ronald H. Rooney, Jo Ann Larsen; Includes bibliographical references (p. 587-608) and indexes
Keywords: Social service; Dịch vụ xã hội